Design and Development of Affordable Salted Fish Drying Machine - NADARAJAH, VSHNU; Dr.Mohd Fahrul Bin Hassan (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This paper presents the development and testing of a prototype salted fish drying machine aimed at enhancing the efficiency and productivity of Small and Medium Industries (SMIs) involved in fish drying. The research encompasses the design, fabrication, and comprehensive testing of the prototype. Performance testing demonstrated significant improvements in drying efficiency and product consistency. This study contributes to the advancement of food processing technology by providing a reliable solution for the fish drying industry.